Challenges and opportunities for advancing Internet access in developing countries while upholding net neutrality. Issue 1 (2nd January 2016) - Sambuli, Nanjira
ABSTRACT: Access to affordable Internet is increasingly a development priority, and even considered a basic right. There are huge economic and social benefits to be reaped from Internet access, as evidenced by gross domestic product contributions, as well as projections. However, a majority of the world's population, most of who are in developing nations, remain unconnected. A crucial policy debate on how to avail Internet access, while upholding and preserving the openness of the Internet, also known as net neutrality, is emerging as state actors, private sector players and civil society alike operate in this space. The practice of zero-rating is one of the most popular approaches to getting the unconnected online. This follows the fact that the mobile phone is the primary device through which the 'next billion' Internet users are expected to get online. The overarching question is whether zero-rating defies the principle of net neutrality, by favouring some content over other content. The challenge for policy makers and regulators in developing countries, as addressed in this paper, is knowing which regulatory frameworks will be needed to expand Internet access to under served communities, without compromising the fundamental principles of a free and open Internet.